ChemInform Abstract: Doping the Alkali Atom: An Effective Strategy to Improve the Electronic and Nonlinear Optical Properties of the Inorganic Al12N12 Nanocage. Issue 10 (11th March 2014) - Niu, Min; Yu, Guangtao; Yang, Guanghui; Chen, Wei; Zhao, Xingang; Huang, Xuri
Abstract Alkali metal doped M@Al12N12 (M: Li, Na, K) nanocages are characterized by B3LYP/6‐31+G(d), MP2 and QCISD ab initio computations.